HUBUNGAN ANTARA GAYA KEPEMIMPINAN KEPALA RUANG DENGAN KINERJA PERAWAT PELAKSANA DALAM MELAKSANAKAN ASUHAN KEPERAWATAN - Windartik, Emyk; Hidayatus Solihah, Nurul (JURNAL KEPERAWATAN SEHAT, 2014)
Leadership style is the group of characteristics used by leader to direct and influence others to have the motivation to achieve organizational goals. Performance is a nurses job in which achieved by a person or group of persons in performing their duties to achieve best result organizational goals. The aim of this research is to know the relationship between leadership style of head nurses and performance of nurses in implementing inpatient nursing care at general hospital Prof.Dr.Soekandar Mojokerto. Design of this research is cross sectional study.Population of this research all nurses in inpatient nursing care at general hospitalProf. Dr.Soekandar Mojokerto. Sample 63 respondent were taken by Non probability type purposive sampling. Data collecting was done by questionaire from adoption Thesis Diah Arruum (2010) and observation sheet. Data analysis was through two steps, those are univariate to see frequency distribution and bivariate to see the relationship (Fisher Exact Test). Statistical test result explain that p (0,512) >α (0,05), there is significant so H0accepted and H1rejected that mean there isn’t a relationship between leadership style of head nurses and performance of nurses in implementing inpatient nursing care at general hospital Prof. Dr.Soekandar Mojokerto. It is suggested to head of nurses to modify their leadership style in appropriate with situation dan condition, so the nurses can be to maintain and further enhance the performance of nurses better.Keyword :Leadership Style, Nurses Performance.